Dumb ideas : a behind-the-scenes exposé on making pranks and other stupid creative endeavors (and how you can also too!) - André, Eric, 1983-; Curry, Dan (Simon & Schuster, 2023)
The minds behind The Eric André Show and Bad Trip reveal the secrets behind their classic pranks and offer tips for novice pranksters to pull off their own stunts such as "Jell-O Surprise," "Benadryl Steaks" and "Amateur Graverobber."